MADRASAH OF RAMADAN, THE BEST EDUCATIONAL INSTITUTION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 6 July 2016 Continue to practice the values and lessons learned during the month of Ramadan in our everyday lives and treat it as the best process to educate one’s heart – soul and consciousness.